Rapid results from micropropagation - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1989)
Technical Memoir No 4: 'Study on the rapid multiplication of plant material', by Dagmar Jordens-Rottger